Testosterone deprivation has neither additive nor synergistic effects with obesity on the cognitive impairment in orchiectomized and/or obese male rats - Hiranya Pintana (2018)
© 2015 Elsevier Inc. All rights reserved. Objective Previous studies demonstrated a correlation between cognitive decline and either testosterone deprivation or obesity. However, the effect of obesity combined with testosterone deprivation on cognitive function has not been investigated. This study investigated the effects of obesity on brain insulin sensitivity, brain mitochondrial function, hippocampal synaptic plasticity and cognitive function in testosterone-deprived male rats. Materials/Methods Male Wistar rats were divided into sham-operated (control) and bilateral orchiectomized (ORX) groups. Rats in each group were further divided into two subgroups to receive either a normal diet (ND) or a high fat diet (HFD) for 4, 8 or 12 weeks. Blood samples were collected to determine metabolic parameters. Cognitive function was tested using the Morris Water Maze Test. At the end of the study, brains were removed to investigate brain insulin sensitivity, brain mitochondrial function and hippocampal synaptic plasticity. Results Both control-obese and ORX-obese rats developed peripheral insulin resistance at week eight, and brain insulin resistance as well as brain mitochondrial dysfunction at week 12. However, the ORX-obese rats developed cognitive impairment and decreased hippocampal synaptic plasticity beginning at week eight, whereas the control-obese rats developed these impairments later at week 12. Although both peripheral and brain insulin resistance were not observed in both the control-lean and ORX-lean rats, impaired cognition and decreased hippocampal synaptic plasticity were found in the ORX-lean rats beginning at week eight. Conclusion These findings suggest that testosterone deprivation has neither additive nor synergistic effects over obesity in the development of cognitive dysfunction in orchiectomized-obese male rats.